Hadith and its position in Herat (Salam International Academic Journal, 2012)
The geographical location and academic importance of Herat: Herat was conquered by Ahmad bin-Qais Tamimi during the caliphate of Omar bin Khattab. The science of Hadith began to flourish in Herat in the second century.The methodologies of scholars of Hadith in Herat: In this part of the article, the writer has argued that there were different and special methodologies used re narration, memorization and documentation of Hadith.The characteristics of Herat school of Hadith: The following topics have been discussed under this title: Great and trustable scholars of Hadith in Herat- the scholars who besides the science of Hadith also had a full grip on Arabic language and have also written books about Arabic language. Unlike the scholars in Balkh. The scholars of Hadith in Herat were, followers of the Shafi juristic school of thought.As part of the characteristics of Herat school of Hadith, the writer has made the following assertions:The city of Herat became a hub of the science of Hadith and an attraction place for students of the science of Hadith.There sprang a large number of scholars of Hadith who were gurus on different branches of the science of Hadith and the science of substantiation of Hadith.A great number of books were written in different aspects of the science of Hadith such as History. Knowledge of Men (narrators). Ete.The Hadith school of Herat gave birth to the jurisprudential school of Herat.Unfortunately, the status of knowledge especially the science of Hadith in Herat has not remained today as was once during the history in this city.
Keywords: Hadith; Herat; Narrator; Methodology of Muhaddithin